Transesterification of oil extracted from freshwater algae for biodiesel production. Issue 15 (2nd August 2016) - Fatima, Nighat; Mahmood, Muhammad Shahid; Hussain, Iftikhar; Siddique, Faisal; Hafeez, Sidra
ABSTRACT: Currently, energy crisis is a burning issue throughout the world, particularly in underdeveloped countries like Pakistan where the demand of conventional fuels has been increasing day by day. The main objective of this project was the production of biodiesel from Algae. Samples of freshwater were collected. The Chlorella species produced 6.26 g oil from 38.23 g of dry weight and the Oedogonium species produced 8.07 g of oil from 38.23 g of dried weight. The biomass obtained after oil extraction was 31.97 g from chlorella species and 30.16 g from Oedogonium species . The fatty acids that were displayed by a gas chromatographic machine in chlorella species were capric acid, nanoic acid, arachidonic acid, behenic acid, and erucic acid and in oedogonium species they were capric acid, butyric acid, behenic acid, luric acid, tridecanoic acid, and arachidonic acid.